Simulasi Komputasi Gerusan Terhadap Kemiringan Baffle Block Pada Bangunan Peredam Energi USBR Type IV Bangunan Spillway - Djunur, Lutfi Hair; Nanda, Abd Rakhim (Universitas Kristen Indonesia Paulus, 2026)
A spillway is a hydraulic structure designed to regulate the flow of water. The energy dissipation structure of a spillway constitutes an essential component of a dam system, functioning to dissipate the kinetic energy of flowing water downstream of the spillway. Energy dissipating devices, such as baffle blocks, are commonly utilized to enhance operational efficiency and to minimize the potential for downstream scour. This study employs computational simulation to investigate the scour behavior resulting from the placement of baffle blocks within the USBR Type IV stilling basin of a spillway, particularly in relation to changes in scour patterns. The research was conducted in a laboratory setting using a scaled physical model to represent the spillway. The experimental results were subsequently validated using SURFER software to develop a numerical model of the USBR Type IV energy dissipation channel. The numerical simulations were carried out using three discharge variations and three configurations of baffle blocks, consistent with the laboratory setup. The analysis evaluates the resulting scour patterns due to the presence of baffle blocks within the stilling basin, assessing whether the simulation outcomes align with experimental observations or exhibit discrepancies. It is expected that this study will provide a more comprehensive understanding of how variations in discharge and the configuration of baffle block placement within a USBR Type IV stilling basin influence the resulting scour patterns in the downstream channel.